Identified serotonergic neurons LCB1 and RCB1 in the cerebral ganglia of Aplysia produce presynaptic facilitation of siphon sensory neurons - Mackey, SL (J Neurosci, 1989)
Several lines of evidence suggest that 5-HT plays a significant role in presynaptic facilitation of the siphon sensory cells contributing to dishabituation and sensitization of the gill- and siphon-withdrawal reflex in Aplysia. Most recently, Glanzman et al. (1989) found that treatment with the 5-HT neurotoxin, 5,7-DHT markedly reduced both synaptic facilitation and behavioral dishabituation. To provide more direct evidence for a role of 5-HT, we have attempted to identify individual serotonergic facilitator neurons. Hawkins (1989) used histological techniques to locate several serotonergic neurons in the ring ganglia that send axons to the abdominal ganglion and are therefore possible serotonergic facilitators. These include one neuron in the B cluster of each cerebral ganglion, which we have identified electrophysiologically and named the CB1 cells. Both glyoxylic acid histofluorescence and 5-HT immunofluorescence indicate that the CB1 neurons are serotonergic. In a semiintact preparation, the CB1 neurons respond to cutaneous stimulation which produces dishabituation and sensitization (such as tail shock) with an increase in firing, which may outlast the stimulation by 15 min. Intracellular stimulation of a CB1 neuron in a manner similar to its response to tail shock produces facilitation of the EPSPs from siphon sensory neurons to motor neurons, as well as broadening of the action potential in the sensory neurons in tetraethylammonium solution. These results strongly suggest that the identified serotonergic CB1 neurons participate in mediating presynaptic facilitation contributing to dishabituation and sensitization of the gill- and siphon-withdrawal reflex in Aplysia.